Rehabilitation and Return to Play of the Athlete after an Upper Extremity Injury - Sameer R. Oak, M.D; Brooks Klein, P.T., D.P.T., S.C.S; Neil N. Verma; Benjamin Kerzner, B.S; Luc M. Fortier, B.A; Neha S. Chava; Michael M. Reinold, P.T., D.P.T., S.C.S., A.T.C., C.S.C.S., C-P.S; Asheesh Bedi, M.D (Elsevier, 2022)
Shoulder and elbow injuries during athletic participation are very common and may require operative intervention if refractory to conservative care. In recovering from these upper extremity injuries, proper postoperative rehabilitation and setting reasonable expectations regarding return to play are very important. This review article focuses on the most common surgically treated shoulder and elbow injuries, including rotator cuff tears, SLAP tears, anterior and posterior shoulder instability, and elbow ulnar collateral ligament tears. Rates of return to play after surgical intervention are encouraging in most professional and recreational athletes but are highly dependent on the severity of injury, as well as the demands and position in sport. Real-world strategies for staged successful rehabilitation are presented and discussed.